ANALYSIS OF MORBIDITY WITH TEMPORARY DISABILITY AMONG WORKERS IN THE MINING AND PROCESSING OF IRON ORE - Sevalnev, A.I.; Oriekhova, O.V.; Pavlenko, O.I.; Sharavara, L.P. (World of Medicine and Biology, 2019)
The purpose of this study was to study the level and structure of morbidity with temporary disability among workers engaged in the extraction and processing of iron ore in the mining and metallurgical complex of Ukraine. Among workers in the mining and processing of iron ore level STP is of 81,87±3,64 to 98,06±2,49 cases, from 806,53±40,51 to 1217,67±63,5 disability days, and in accordance with the scale of assessment of indicators of morbidity for L. E. Notkin characterized by day, as an average, on occasions, as high. In the structure diseases of workers employed in the mining and processing of iron ore in the first place are diseases of the respiratory system, the second place is occupied by diseases of musculoskeletal system and connective tissue, in third place − injury and poisoning. At the enterprise of ferrous metallurgy for research period the level of morbidity with temporary disability was 106,15±4,34 cases and 1388,62±70,9 days of disability per 100 employees, that according to the scale of assessment of morbidity with temporary disability rates by L. E. Notkin characterized as above average and high, respectively. In the structure of morbidity the largest specific weight has respiratory diseases, injuries, diseases of the musculoskeletal system. Studies show the need to establish dynamic supervision, monitoring of health status of each individual employee for the purpose of timely detection of early manifestations of occupational disease and mandatory rehabilitation treatment for the purpose of preservation of working capacity of the worker in his profession, prospects for further research aimed at the development and implementation of preventive measures.